Construction And Validity Of The Hypnoteaching-Based Learning Model: A Development Study In Elementary Schools - Hisbullah Hisbullah; Sitti Nadirah; Aniati Aniati; Ali Rahman (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This study aims to develop and validate the Hypnoteaching-Based Learning model in strengthening character in elementary schools. It is a research and development study conducted using the ADDIE model. The subjects of this study were students at MI Darul Khaeriyah Towondu in Luwu Regency, South Sulawesi. The validity of the model was assessed by three experts: learning design experts, character education implementation experts, and hypnoteaching experts, who evaluated and provided assessments of the developed Hypnoteaching-Based Learning model. The results of the study showed that the Hypnoteaching-Based Learning model achieved high validity qualifications, with a validity percentage of 90.42%. The model combines learning syntax with hypnotic syntax to design instructional steps that enhance students' character. The implications of this research indicate that the Hypnoteaching-Based Learning model can be an effective alternative to improve learning and character development in elementary schools. Further research and implementation of the Hypnoteaching-Based Learning model are expected to yield significant benefits in the field of education.